Unsteady Stagnation-Point Flow of a Viscoelastic Fluid in the Presence of a Magnetic Field - F. Labropulu (International Journal of Mathematics and Mathematical Sciences)
The unsteady two-dimensional stagnation point flow of the Walters B' fluid impinging on an infinite plate in the presence of a transverse magnetic field is examined and solutions are obtained. It is assumed that the infinite plate at y=0 is making harmonic oscillations in its own plane. A finite difference technique is employed and solutions for small and large frequencies of the oscillations are obtained for various values of the Hartmann's number and the Weissenberg number.